Negotiating Motherhood In Flora Nwapa’s Efuru and Buchi Emecheta’s The Joys Of Motherhood - Brenda Carabuena; Chloe Cadiz; Diana Jane Pajulas; Mary Jane Mayono (JEE (Journal of English Education), 2025)
This paper explores the complexities of motherhood and identity in Nigerian literature through a comparative analysis of Efuru by Flora Nwapa and The Joys of Motherhood by Buchi Emecheta. Using textual analysis and drawing from Intersectional Feminism and Identity Negotiation Theory, the study examines how gender, race, and class intersect to shape women’s identity. Both novels portray motherhood as a layered identity shaped by societal expectations. In Efuru, the protagonist asserts her individuality despite cultural norms that prioritize maternal roles. In contrast, The Joys of Motherhood reveals how the protagonist Nnu Ego’s identity is reduced to motherhood alone. The findings suggest that while motherhood is revered, it often restricts women’s agency, forcing them to constantly negotiate their identities.